'A different fan group': the performance of a Brazilian gay organized fan group. (3rd October 2022) - Aguiar dos Anjos, Luiza; da Silva, Silvio Ricardo
ABSTRACT: Football in most parts of the world is historically associated with men and cisheteronormative masculinity. The virility demanded and valued in it is often accompanied by an endorsement of chauvinism and homophobia. The engagement of those who do not fit the standard is surrounded by obstacles. In view of this scenario, the Brazilian organized fan group Coligay, formed predominantly by men identified as homosexuals, was an unusual and transgressive initiative. The group was founded in 1977 and for approximately five years it was present in the stadiums supporting the traditional club Grêmio Foot-Ball Porto Alegrense. With demonstrations that explore aesthetic elements traditionally associated with homosexuality, they destabilized the legitimate and predominant model of a fan, and the norm that naturalizes football as a stronghold of cisgender and heterosexual men. From the crossing of oral sources and records from periodicals, we analyse such performance from the perspective of gender studies.